Some ascidians from Indonesian marine lakes (Raja Ampat Islands, West Papua) - Monniot, Françoise (Zootaxa, 2009)
A small collection of ascidians from Indonesian marine lakes in the Raja Ampat Islands, West Papua province, was made by biologists from the university of California, Merced and Coral Reef Research Foundation, Palau during a marine lakes macro-invertebrate diversity survey. It comprises 19 species. Some of them previously described show some modifications of their anatomical characters which may be due to a lower salinity and pH of the lake water or perhaps to evolution in situ. Some specimens (Aplousobranchia) could not be assigned to a species, the samples being too small, the larvae absent, and a possible modification in the number or shape of the calcareous spicules may occur. They are nevertheless described.